Combo Energético Sustentável: o caso do assentamento Celso Lúcio Moreira da Silva comunidade Carinhosa - Martins, Lucas Carvalho (2020)
The public politics together with taken actions and projects have an objective that is to solve public matters which are present in the society. It was spotted some public problems which are more common in the settlement of the Agrarian reform from Brazil such as: low income from lot of land, high cost of the power and thermal electricity, lack of access to the electric power, young rural students escaping due to the activities which they are paid for and lack of access to technical assistance. These problems motivated the creation and the planning of a project proposal together with the public politic of Pronafeco, which is a politic that finances project of clean energy to the familiar agriculture. This project was named “Sustainable Energetic Combo” which is aimed to turn the rural settlement products self-sufficient in the electric power production, biofuel and biofertilizer through two clean technologies: solar energy and low scale biodigest, both of them installed in each lot. The project was planned and directed to the Agrarian Reform Celso Lúcio Moreira da Silva in the region of Uberlândia -MG which data was provided through documental analyse of the project “Apoio a continuidade do Núcleo de Estudos em Agroecologia e Produção Orgânica da Universidade Federal de Uberlândia”. The methodoly presented in this project is marked as quantity and quality and its result was from a case study about the planning to propose the project through the methodoly of the cycle supervision of public politics together with the supervision of the project planning. The purchasing and the biodigestor construction resulted an amount of R$ 3,770.66 and the purchasing and installation of the solar energy system were in R$ 8,160,00 which resulted an amount of R$ 11,930,66 to apply the two technologies in an unique lot. It was simulated three different scenarios with the same technologies. The scenario which showed economic and financial positive viability was the scenario number one, which the residents finance the technologies and there is no production of the carbon credits. This scenario showed that the application of this project in the settlement would be valuable.The scenario 3 and 4 were simulated with the same technologies. However, there was carbon production which is not feasible. The project presented high level of sustaintability calculating a reduction of 1,604 tones of annual carbon which would not be thrown in the atmosphere, which engages very well with the practice of the residents from the settlement studied as they themselves look for the system of the agroecologic production.